Consumption of obesogenic foods in non‐Hispanic black mother–infant dyads. Issue 1 (18th June 2017) - Kay, Melissa C.; Wasser, Heather; Adair, Linda S.; Thompson, Amanda L.; Siega‐Riz, Anna Maria; Suchindran, Chirayath M.; Bentley, Margaret E.
Abstract: Obesity continues to be a problem in the United States. Of particular concern is the epidemic of early childhood obesity. A significant predictor of child diet is maternal diet, but little is known about this relationship during infancy. This study examined the association between maternal and infant consumption of key food groups from 6 to 18 months using data from the Infant Care, Feeding, and Risk of Obesity Study, a prospective cohort of 217 non‐Hispanic black, low‐income, first‐time mothers. Using data from 24‐hr dietary recalls collected during in‐home visits at 6, 9, 12, and 18 months, we assessed longitudinal associations between mother and child intake of both energy‐dense, nutrient‐poor (obesogenic) food groups and fibre‐, nutrient‐rich food groups using random intercept logistic regression. Both mothers and their infants had high intake of sugar‐sweetened beverages, desserts, and sweets and low intake of vegetables and whole grains. Infant consumption of key food groups was strongly associated with maternal consumption, suggesting the need for focused interventions to target maternal diet as a pathway to decreasing risk for the establishment of poor dietary patterns early in life.